2022
DOI: 10.1253/circrep.cr-22-0045
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Reference Ranges of Non-Invasive Myocardial Work Indices in Newborns

Abstract: Background: Myocardial work (MCW), estimated using non-invasive pressure-strain loops, is a novel approach for assessing left ventricular function. MCW offers potential advantages over left ventricular ejection fraction and global longitudinal strain (GLS). This study aimed to establish a reference range for MCW in newborns. Methods and Results:Overall, 113 healthy newborns (mean [±SD] birth weight 3,120±378 g) were included in the study. After entering peripheral systolic and diastolic blood pressure (BP) val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…There were no significant differences between the 2 groups concerning gestational age, length, weight, or body surface area. The MCW data showed that GWI and GCW, including z-score using a normal range in the neonatal period, 16 was significantly higher in infants with GDM and <6.5% HbA1c than infants with GDM and >6.5% HbA1c (Table 3B). The color M-mode data showed that IVPD and IVPG were higher in unclear.…”
Section: Mcw Of Infants With Gdmmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant differences between the 2 groups concerning gestational age, length, weight, or body surface area. The MCW data showed that GWI and GCW, including z-score using a normal range in the neonatal period, 16 was significantly higher in infants with GDM and <6.5% HbA1c than infants with GDM and >6.5% HbA1c (Table 3B). The color M-mode data showed that IVPD and IVPG were higher in unclear.…”
Section: Mcw Of Infants With Gdmmentioning
confidence: 99%
“…[13][14][15] Recently, we established the reference ranges for MCW parameters in healthy newborns. 16 Because there have been few studies reporting non-invasive MCW measurement in infants born to mothers with GDM (termed "infant with GDM") using the new definition of GDM, that was the focus of the present study.…”
Section: Other Measurementsmentioning
confidence: 99%